Prima persona plurale. La Francia e Gli anni di Annie Ernaux (Materiali di Estetica. Terza serie, 2017)
The work of the French writer Annie Ernaux, Gli anni (translated in 2015), is the narration in “the first plural person” of the life of the author and of her nation, France. In a strict sense, it is not an autobiography or a history book. However its value lies in the (successful) attempt to make interact the two genres, in order to express with the word “us” the fullness of an existence lived in that precise becoming of society. The encounter is reached thanks to a personal writing style: dry, sharp, merciless. A mention to her other books, L’altra figlia, Memoria di ragazza, Il posto complete this essay.